Providing Laboratory Monitoring of Environmental Objects During the XXII Olympic Winter Games and XI Paralympic Winter Games in Sochi - A. Yu. Popova; A. A. Gorsky; A. S. Gus'kov; G. E. Ivanov; L. V. Chikina; V. S. Stepanov; E. S. Pochtareva; O. I. Aksenova; L. I. Shcerbina; V. V. Parhomenko; O. A. Kulichenko; N. S. Komarova; et al. (Эпидемиология и вакцинопрофилактика)
The organization of laboratory environmental monitoring in the pre-Olympic period and during the XXII Olympic winter games and XI Paralympic winter games 2014. The results of radiation monitoring during the construction of sports and infrastructure facilities Sochi. Study analyzed the procedure for compliance with hygienic standards and additional indicators of drinking water, food, food raw material and other objects.